2022
DOI: 10.1128/aem.01619-22
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Diatom-Bacteria Consortia in Synthetic Plankton Communities

Abstract: The marine food web is fueled by phototrophic phytoplankton. These algae are central primary producers responsible for the fixation of ca. 40% of the global CO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…They represent two most abundant genetic clades in the marine environment which differ in their utilization and metabolization of DMSP (Scheme 2). 28 The strain CS4 contains the proteins for both the DMSP demethylation (DmdA, B, C, and D) and cleavage pathway (DddW and DddP) (Scheme 2 and Fig. S18, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent two most abundant genetic clades in the marine environment which differ in their utilization and metabolization of DMSP (Scheme 2). 28 The strain CS4 contains the proteins for both the DMSP demethylation (DmdA, B, C, and D) and cleavage pathway (DddW and DddP) (Scheme 2 and Fig. S18, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…They represent two most abundant genetic clades in the marine environment which differ in their utilization and metabolization of DMSP (Scheme 2). 28…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether any of our isolates had prior reports of being algicidal, we conducted a literature review. This revealed that antagonistic activity against algae has been reported previously in eight of the genera of the WEC isolates, including Ponticoccus (Chi et al ., 2017), Thalassospira (Lu et al ., 2016), Halomonas (Zheng et al ., 2018), Marinobacter (Zheng et al ., 2018; Deng et al ., 2022), Vibrio (Li et al ., 2014), Pseudomonas (Aiyar et al ., 2017; Kim et al ., 2018), Alteromonas (Wang et al ., 2016; Shi et al ., 2018), and Maribacter (Wang et al ., 2016; Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we observed a robust growth inhibitory effect of M. adhaerens against Chaetoceros sp. PLY617, despite this bacterium more commonly being considered a diatom commensal (Gärdes et al ., 2012; albeit a subtle inhibitory effect on Coscinodiscus radiatus growth by this bacterium was recently reported; Deng et al ., 2022). Indeed, this effect was only observed when cells were first grown on medium made up of autoclaved diatoms.…”
Section: Discussionmentioning
confidence: 99%
“…As with land plants and other host–microbial systems, microalgal activity, productivity, and stability are closely tied to surrounding microbial communities (Seymour et al ., 2017). However, a predictive understanding of microbial community interactions with algae is still limited (Astacio et al ., 2021; Deng et al ., 2022; Prabhakara & Kuehn, 2022).…”
Section: Introductionmentioning
confidence: 99%